Implementation of a Modelica library for simulation of electromechanical actuators for aircraft and helicopters - Linden, Franciscus van der; Schlegel, Clemens; Christmann, Markus; Regula, Gergely; Hill, Christopher Ian; Giangrande, Paolo; Maré, Jean-Charles; Egaña, Imanol (2014)
The goal of the A2015 library presented in this paper is to develop a Modelica based, tool-independent standard for electromechanical actuators (EMA). This will contribute to the establishment of a “common language” throughout the development of EMAs for aircraft and helicopters and through the supply chain. All stages of the design and validation process (conceptual design, specification, development and validation) are covered. The modeling approach addresses specific aspects of the EMA design process not covered by existing tools. The library scope, engineering need and implementation are described. Modeling of selected EMA components is discussed in more detail. An application example of the library is given (linear actuator, A320 aileron)